Homer G. Smith papers - Smith, Homer G.
Correspondence, oral history transcripts, notes, and printed material pertaining to Smith's book, A Challenge to U. S. Agriculture: Building the Cooperative Production Credit System. Subjects include the U.S. Farm Credit Administration Production Credit System and the organization of local farmer-owned and rancher-owned credit cooperatives.
Accountant, banker, and credit administrator.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Farm Credit Administration. -- Production Credit Division; Agricultural credit -- United States; Agriculture -- United States; Agriculture -- United States -- Finance; Accountants; Administrators; Bankers